The Effectiveness of Nutrition Education using Flipchart Media on Attitudes of Type 2 Diabetes Mellitus Patients Hospitalized at Inche Abdoel Moeis Hospital - Sonia Noer Safera; Sepsina Reski; Arifin Hidayat (Formosa Journal of Science and Technology, 2023)
Nutrition education is the process of training skills or sharing knowledge to help patients modify diet and change behavior. Attitude can affect the successful management of diabetes mellitus. The aim of the study was to see changes in patient attitudes before and after providing nutrition education using flipcharts and leaflets. Quantitative research design with quasi-experimental methods, research design matching pretest-posttest control group design. The study was conducted at the IA Moeis Hospital with a sample of 36 hospitalized patients. The research instruments used were attitude questionnaires, flipcharts and leaflets. The results of this study showed that after providing education using flipcharts and leaflets, the patient's attitude was in the good category, 18 people (100%). The results of the average value of the media, providing education using leaflet media is more effective than leaflet media.